Atmosphere, weather and climate - Barry, Roger G . (Routledge, 1987)
Atmosphere, Weather and Climate is the essential introduction to weather processes and climatic conditions around the world, their observed variability and changes, and projected future trends. Extensively revised and updated, this eighth edition retains its popular tried and tested structure while incorporating recent advances in the field. From clear explanations of the basic physical and chemical principles of the atmosphere, to descriptions of regional climates and their changes, Atmosphere, Weather and Climate presents a comprehensive coverage of global meteorology and climatology.